2005
DOI: 10.1079/ahr2005106
|View full text |Cite
|
Sign up to set email alerts
|

Porcine circovirus diseases

Abstract: Porcine circovirus type 2 (PCV2) is a member of the family Circoviridae, a recently established virus family composed of small, non-enveloped viruses, with a circular, single-stranded DNA genome. PCV2, which is found all over the world in the domestic pig and probably the wild boar, has been recently associated with a number of disease syndromes, which have been collectively named porcine circovirus diseases (PCVD). Postweaning multisystemic wasting syndrome (PMWS), porcine dermatitis and nephropathy syndrome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
412
0
27

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 518 publications
(451 citation statements)
references
References 135 publications
(258 reference statements)
12
412
0
27
Order By: Relevance
“…Scott et al (2006) reported more prevalent loss of body condition in the straw-bedded system than in the fully slatted system and associated it with poorer hygiene and wasted animals, generally associated with Postweaning Welfare assessment on growing pig farms Multisystemic Wasting Syndrome (PMWS). Knowing that PMWS most commonly affects pigs at 2 to 4 months of age (Segalé s et al, 2006), this hypothesis is reinforced in the study by the fact that few cases of poor body conditions were recorded at the end of the growing period.…”
Section: Discussionmentioning
confidence: 75%
“…Scott et al (2006) reported more prevalent loss of body condition in the straw-bedded system than in the fully slatted system and associated it with poorer hygiene and wasted animals, generally associated with Postweaning Welfare assessment on growing pig farms Multisystemic Wasting Syndrome (PMWS). Knowing that PMWS most commonly affects pigs at 2 to 4 months of age (Segalé s et al, 2006), this hypothesis is reinforced in the study by the fact that few cases of poor body conditions were recorded at the end of the growing period.…”
Section: Discussionmentioning
confidence: 75%
“…A razão pela qual apenas alguns entre os animais infectados pelo PCV2 desenvolvem a doença na sua forma aparente ainda não está clara. Há indícios de que um perfil alterado de citocinas nos tecidos linfóides de determinados indivíduos -incluindo um aumento de interleucina 10 e a incapacidade de produzir interferon logo no início do processo infeccioso -esteja relacionado à expressão completa da SMDS (Segalés et al 2005).…”
Section: Discussionunclassified
“…(Segalés et al 2004a). Infecções virais e bacterianas associadas ao PCV2 ocorrem com freqüência em rebanhos afetados pela SMDS (Segalés et al 2005), predispostas por um estado de imunodepressão induzido pelo PCV2 (Segalés et al 2004b). As doenças do ouvido dos suínos têm recebido pouca atenção veterinária por envolverem órgãos de difícil acesso ao exame e por, aparentemente, não estarem associadas com perdas econômicas significativas.…”
unclassified
“…Although gastric ulceration of the pars oesophagica has been reported in PMWS-affected pigs (Segalés et al 2000), no direct relationship between these lesions and PCV2 has been established (Segalés et al 2005). The aim of the present study was to establish an association between PCV2 infection and the development of gastric ulcers in PMWS affected pigs.…”
Section: Introductionmentioning
confidence: 88%
“…Among the methods used to detect PCV2 in tissues and to correlate it with lesions, the in situ hybridization (ISH) and immunohistochemistry are the most widely used , Rosell et al 1999, Segalés et al 2005). Considering the hypothesis in which the mucusproducing cells of the gastric glandular zones are targets for the PCV2 infection in the stomach of pigs, the necrosis induced by PCV2 in these cells may be associated with the decreased stomachal pH by the imbalance of the sodium bicarbonate buffering system and subsequently, with the ulceration of the pars oesophagica.…”
Section: Discussionmentioning
confidence: 99%